“We die for kula”—An object-centred view of motivations and strategies in gift exchange - Kuehling, Susanne (Waka Kuaka, 2017)
This paper examines the value of kula objects by focusing on the perspectives of islanders from the southern kula region. By linking kula practice to death and life, I argue that the objects' value is complex: material, sentimental and personal, created by partnerships in time and space. Kula valuables are valuable because they are managed by the most respected elders, occupy the minds of the those considered the most intelligent people of the region, and serve to build relationships, as well as test the honesty and integrity of individuals. They are also valued for their capacity to provide hospitality and solidarity, to repair conflicts and to express love and grief.